A cross-sectional qualitative study exploring how celebrity brand ambassadors influence customer loyalty - Padayachy, Yugendri (The IIE, 2017)
The term Celebrity Brand Ambassadors has become a term with many uncertainties around it. This research paper will help give clarity to the term as well as give a better understanding as a whole. The phenomenon of using celebrity brand ambassadors such as Oscar Pistorius and Brad Pitt reflects on the brands personality as well as the brands values that these personalities are representatives of. Therefore, celebrity brand ambassador transgressions could either positively or negatively influence the brands image as well as the consumer’s perception about the brand. The reason for the research question coming about is to learn about what shapes an individual’s perceptions about real life situations (Leana, 2014). Such as, what tools individuals use to make a personal decision and the factors that may influence those decisions in life. To gain more insight, brands may face numerous challenges after experiencing a crisis or confronted with negative press coverage. Undoubtedly the problem of celebrity brand ambassadors who either positively or negatively influences a shopper’s loyalty is imperative to an organisation, as it is the company’s duty to select a brand ambassador to represent their brand, where it could be seen that celebrity brand ambassador transgressions have a more important influence on a consumer’s perception of the brand ambassador than on the brand itself. Therefore the problem being explored throughout this cross-sectional qualitative research study is to, discover if celebrity brand ambassadors have a positive or negative influence on a customer’s decision making about the purchasing of a product. This research paper aims to address these main issues and further aims to gain insight on how to approach such problems. This research paper represents the opinions of a sample of consumers from Pretoria West demographic and further aims to use the data gathered to bring forward suggestions that celebrity brand ambassadors do not influence a customer’s loyalty by providing suggestions on how companies could use this strategy to better improve their marketing and branding efforts. This could help improve or increase equity among their customers. The research conducted comprised of two focus groups and structured interviews. This was chosen in order to gain an in depth understanding of qualitative data as the nature of the research is qualitative. The population consisted of millennials within the Pretoria West region, and the sample sizes were picked at random as to avoid any form of bias in the study. Key findings that were most significant during the research were that participants all agreed that celebrity brand ambassadors do not influence their buying decisions because celebrity brand ambassadors do not create brand awareness and sustain customer loyalty since for them to an extent the brand loses its essence because of a celebrity brand ambassador. As well as celebrities on a whole brought short term joy to the consumers and left a larger stain of negative associations to the influence it has on a consumer’s decisions to purchase a product. An important theme mostly affected was the diminishing loyalty among consumers and the influence a celebrity brand ambassador has on their loyalty. Loyalty was judged upon the value and quality experienced which was further affected by price increases and the positive and negative influences of these unities. This theme is a common theme that is a main pillar which forms Aaker’s brand identity model (2009).
Keywords: Celebrity Brand Ambassadors; Brand Value; Branding; Brand Awareness; Customer Loyalty